Power demand response in the context of smart home application. (1st February 2022) - Yu, Biying; Sun, Feihu; Chen, Chen; Fu, Guanpeng; Hu, Lin
Abstract: Smart home, is expected to bring great changes to people's lifestyles. By shifting the timing of residents' electricity consumption, smart home can improve the flexibility of the power load, and provide significant potential for power demand responses. These responses can substantially mitigate peak-to-valley power demand gaps and household electricity costs. However, the extent of the likely impacts from smart home participating in power demand response remains unknown, and very limited research has been conducted thereon. Therefore, this study attempts to explore the potential changes in peak-to-valley electricity consumption and electricity costs owing to smart home, by developing a multi-objective smart home integrated management model with the consideration of appliances and household electricity consumption behavioral heterogeneity. The survey data collected in China was employed in the empirical analysis. Results show that smart home participating in power demand response can reduce peak load by 29.3%–49.3%, which is up to 149 GW, and the peak-to-valley difference could be decreased by 37.5%–78.2%. However, significant variance exists for the smart home impacts among households with different structures and individual occupations. Teachers, freelancers, and homeworkers contribute more to this reduction. In addition, the peak-to-valley difference after introducing smart home would shrink from -80.7%–-68.5% to -29.2%–-23.9% for areas with the time-of-use price policy, which performs better than the areas without time-of-use price policy. Regarding the economic benefits, smart home participating the demand response could reduce the investments in the power supply and power grid by 1.13–1.19 trillion RMB in China. Highlights: The impacts of smart home participating in power demand response is evaluated. A smart home integrated management model is established for power demand response. The heterogeneous characteristics of different in-home devices and behaviors are considered. Smart home optimization can reduce peak load by 29.3%–49.3%. Smart home optimization can reduce investment by up to 1.2 trillion RMB.